High resolution wind atlas for Nakhon Si Thammarat and Songkhla provinces, Thailand - Jompob, Waewsak (ScienceDirect, 2016)
In this work, a high resolution wind atlas for Nakhon Si Thammarat and Songkhla provinces in southern Thailand was developed using combined mesoscale, MC2, and microscale, MsMicro, modeling techniques. The model inputs consist of long-term statistical climate data, i.e. the NCEP/ NCAR database, high resolution topography and land cover data. The 200 m resolution wind resource maps were validated with observed mean wind speeds from 10 met stations located along the coastlines of the territory studied. These comparisons have shown that the wind atlas provides a good representation of the wind resource throughout the territory of Nakhon Si Thammarat and Songkhla provinces, Thailand. The technical power potential and potential annual energy production are then identified. Results from the technical power potential at 80 m above ground level show that a total of 1374 MW of wind farms, generating annually 3.6 TWh of electricity, could be installed; while 407 MW of small wind turbines (50 kW), generating annually 1.0 TWh of electricity, could be installed.